Європейський досвід захисту прав інтелектуальної власності - Дєєв, С. Д. (ХНУРЕ, 2019)
The paper is addressed the issue of the practice of protecting of Intellectual Property rights in the European Union. Different of European Union and Ukraine law is analyzed. Standards of the European Union is investigated and the set of steps for Ukraine law improvement is proposed.